Effects of Pyraclostrobin on Growth and Yield of Curly Red Chili (Capsicum Annum L.) - Arizal Nur Hardiansyah; Endang Sulistyaningsih; Eka Tarwaca Susila Putra (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Curly red chili was one of vegetable commodities in Indonesia used for seasoning of home cuisine, food industry, and pharmaceutical industry. Curly red chili cultivation needed fungicide to prevent fungal disease. Pyraclostrobin was a fungicide which could overcome fungal attack and improve plant growth. This research was conducted to study the effectiveness of pyraclostrobin application on vegetative growth of curly red chili plant. Research had been done in farmer’s land in Kemiriombo Village, Dukun Sub District, Muntilan District, Magelang Regency from December 2013 to June 2014. The treatments were assigned in the Randomized Complete Block Design with three replications. The treatments consisted of P1: pyraclostrobin doses 1.5 kg ha-1, 30 and 90 days after planting (dap), P2: pyraclostrobin 1.5 kg ha-1 at 30, 60, and 90 dap, P3: pyraclostrobin 1.5 kg ha-1, at 15, 30, 60, and 90 dap, P4: pyraclostrobin 3 kg ha-1, at 30 and 90 dap, P5: pyraclostrobin 3 kg ha-1, at 30, 60, and 90 dap, P6: pyraclostrobin 3 kg ha-1, at 15, 30, 60, and 90 dap, and P0: control (no treatment). Data were analyzed by orthogonal contrast test with α=5%. The result indicated significant different in the dry weights of root, stem, leaf, and total yield at 12 weeks after planting; number of flower at 9-11 week after planting, 14 week after planting, and 18-21 week after planting; and number of fruits at 10-12 week after planting, 15, and 16 week after planting. The application of pyraclostrobin at all dosages could increase IAA content. The numbers of flower and fruit were influenced by the increasing of IAA content in plant tissue, but did not affect the yield.